The Marble Faun; Or, The Romance of Monte Beni - Volume 1 - Hawthorne, Nathaniel, 1804-1864 (Salt Lake City, UT : Project Gutenberg, 2006)
"The Marble Faun; Or, The Romance of Monte Beni - Volume 1" by Nathaniel Hawthorne is a romance published in 1860. Set in a fantastical Italy, the story follows four characters: the mysterious painter Miriam, innocent copyist Hilda, rationalist sculptor Kenyon, and Donatello, a count who strangely resembles an ancient marble faun. As Miriam is pursued by a threatening figure from her past and Donatello's possible connection to mythical ancestry emerges, the narrative weaves together elements of fable, gothic mystery, and pastoral romance against an Italian backdrop. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_Marble_Faun
Release date is 2006-02-26
Produced by Michael Pullen and David Widger
Keywords: Psychological fiction; Love stories; Nobility -- Fiction; Rome (Italy) -- Fiction; Artists -- Fiction; Murder -- Fiction; Americans -- Italy -- Fiction; Women art students -- Fiction